321. Role of Diagnostic Reference Levels (DRLs) in Nuclear Medicine: The experience of INT Pascale in Naples. (December 2018) - D'Ambrosio, L.; Gaballo, P.; Prisco, A.; Di Gennaro, F.; Lastoria, S.
Abstract : Purpose: DRLs provide guidance regarding appropriate or conventional levels of radiation dose to be delivered to patients. DRLs should be used to supplement, not replace, professional judgment and do not provide a dividing line between good and bad medicine but they offer a tool to educate imaging clinics on best practices. We assert that national DRLs have a limited role to promoting optimal practice, that is sufficient image quality at the minimum dose. In contrast, each clinic can set local DRLs based on local resources (imaging equipment, time for examinations). This study was focus precisely on local reference levels as guidance to ensure that certain radiation doses not exceed and to optimize quality images with to improve patient care. Methods: The data of all diagnostic examinations were collected from 2012 and 2016. The 75th percentile of the distribution and the average administrated activity were calculated and the average effective dose per examination were estimated using dose conversion factors. Results: For each examination the average administered activity was lower than national DRLs, except for 99mTc-MAA pulmonary perfusion imaging which was larger for the need of tomographic acquisition. Furthermore, during last five years the average administered activity decreased with improvements in imaging equipment and the review regularly of local reference levels. For the 2 common examinations, 18F-FDG whole body and 99mTc-MDP bone planar, the radiation dose estimated according to models recommended in ICRP106 were 5, 1 mSv and 4, 2 mSv, respectively. Conclusions: The main outcome of this internal survey is that local reference levels should continuously reconsidered to optimize protocols, to ensure best practices and to reduce dosimetry to patient and workers.